Optimizing Staple Food Distribution Efficiency using the Traveling Salesman Problem in Local Government - Jufri, Moh; Nasrullah; Rodiyah, Asyatir (Faculty of Engineering and Computer Science, 2025)
The equitable distribution of essential goods in Indonesia’s remote and archipelagic regions faces significant logistical challenges, primarily due to geographical complexity, limited transportation infrastructure, and unpredictable weather conditions. This study adopts the Travelling Salesman Problem (TSP) model to optimize inter-island aid distribution routes, with delivery locations modeled as a complete weighted graph. Inter-location distances are calculated using the Haversine formula based on actual geographical coordinates. The Path Cheapest Arc heuristic algorithm, implemented via Google OR-Tools, is employed to efficiently generate near-optimal routes. The optimization results show a reduction in travel distance by 22.7% (from 256.7 km to 198.4 km), accompanied by a decrease in estimated travel time from 10.27 hours to 7.94 hours, and a reduction in fuel consumption from 102.7 liters to 79.4 liters. These findings empirically demonstrate that TSP optimization can significantly reduce travel distance and distribution time in the context of maritime logistics. The integration of graph theory, optimization algorithms, and interactive route visualization not only enhances computational efficiency but also provides practical benefits for policymakers in the public sector. This methodological framework has the potential to be replicated for distribution scenarios in other remote regions, while also strengthening data-driven decision-making in governmental logistics planning.